2021
DOI: 10.18517/ijaseit.11.3.13705
|View full text |Cite
|
Sign up to set email alerts
|

Ukrainian MOOC: Quantitative and Thematic Analysis of Online Courses

Abstract: The article is devoted to the quantitative analysis of the courses hosted on Ukrainian mass open online courses (MOOC) platforms. It has been found that MOOC, being an effective mechanism of lifelong learning, provides the development of general and professional competencies; it supports principles of openness and accessibility. We have analyzed the online courses located on such well-known Ukrainian online platforms as Prometheus, EdEra, and the Open University of Maidan. It has been found that Ukrainian onli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
6
0
1
Order By: Relevance
“…The thematic area was chosen as a criterion for grouping online courses and further processing of the obtained statistical data. In the process of research, the obtained data were compared with similar studies, presented in the work by S. Sharov et al [8].…”
Section: Methodsmentioning
confidence: 89%
See 3 more Smart Citations
“…The thematic area was chosen as a criterion for grouping online courses and further processing of the obtained statistical data. In the process of research, the obtained data were compared with similar studies, presented in the work by S. Sharov et al [8].…”
Section: Methodsmentioning
confidence: 89%
“…In Ukraine, online courses and distance education in general are gradually gaining popularity. The analysis of previous studies [8] revealed that 235 online courses were developed on similar MOOC through 2014-2020. As of May 2020, there were 130 online courses on Prometheus platform, 49 courses on EdEra online platform, and 56 courses on OUM platform, which is 55%, 21% and 24% respectively of the total number of online courses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Advanced training can help teachers develop all the necessary skills to work with various Google applications; it can help them consider the main methods of increasing the educational motivation of students, and ensure the exchange of ideas between practicing teachers. Massive open online courses, which have now become quite popular, will be useful for teachers' self-development [29]. The work by [9] offers teachers to take online trainings in order to increase their awareness regarding the possibilities of Google Workspace.…”
Section: Discussionmentioning
confidence: 99%